A survey on the cryptanalysis of the advanced encryption standard - Z’aba, Muhammad Reza; Maarof, Mohd. Aizaini (UTM, 2006)
The Advanced Encryption Standard (AES) is a cipher adopted by the National Institute of Standards and Technology (NIST) to secure classified United States (US) digital government documents. A cipher is an algorithm that converts information (plaintext) to unreadable (ciphertext) form and vice-versa. The AES has also been employed in other areas such as to secure information in smart cards and online transactions. This year marks the fifth year that the AES has been adopted as a standard. During that period, many attacks have been performed on the cipher. However, none have fully broken the complete round cipher. All of the attacks were launched on reduced-round version and the complexity is compared to that of brute force. Brute force is an attack that tries every possible value of the key of the cipher. Therefore, it serves as the upper bound on the attack on block ciphers. In this paper, we will review some existing cryptanalytic attacks on AES